Un monument funéraire du Haut-Empire aux confins de la cité des Carnutes à Boinville-en-Mantois (Yvelines) - Aurélie Laurey; Vanessa Brunet; Mélanie Demarest; Céline Mauduit (Gallia)
The rescue excavation of rue du Bois de la Planté, at Boinville-en-Mantois (78), carried out in 2016 over a surface of 1.5 ha, brought to light several diachronic occupations, dating from the Early Mesolithic, the Middle Neolithic, the First Iron Age and the Roman Period. The main discovery of this preventive operation is a funerary enclosure surrounding a square central building, dating from the Roman Period. Four burials, two secondary cremation deposits and two inhumations of adult and immature individuals, were uncovered in this area. Two of them are outstanding on account of the not very frequent and opulent offerings placed next to the deceased (metallic folding seat, gold ring, gold holding-amulet...). Two other original installations were observed: a small offering pit and a large buried monolithic limestone block. It is important to mention a last structure, near the enclosure, identified as a secondary cremation deposit with a libation pipe. This funerary monument, which was probably raised by and for a local elite personage, between the end of the 2nd and the beginning of the 3rd c. AD in Lyonnaise Gaul/Gallia Lugdunensis, presents specific structural features and deposits.